Proceedings of the 2008 ACM Symposium on Virtual Reality Software and Technology 2008
DOI: 10.1145/1450579.1450612
|View full text |Cite
|
Sign up to set email alerts
|

A psychophysically calibrated controller for navigating through large environments in a limited free-walking space

Abstract: Experience indicates that the sense of presence in a virtual environment is enhanced when the participants are able to actively move through it. When exploring a virtual world by walking, the size of the model is usually limited by the size of the available tracking space. A promising way to overcome these limitations are motion compression techniques, which decouple the position in the real and virtual world by introducing imperceptible visual-proprioceptive conflicts. Such techniques usually precalculate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 20 publications
(24 reference statements)
6
28
1
Order By: Relevance
“…Further, they compared different generalized approaches for redirected walking and proposed improvements to the S2C algorithm [8]. Engel et al [3] proposed a psychophysically calibrated controller that employs a cost function based on the noticeability of redirection. Nitzsche et al [12] and Su et al [19] suggested an approach that dynamically minimizes the introduced curvature, but does not make imperceptibility a primary goal.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, they compared different generalized approaches for redirected walking and proposed improvements to the S2C algorithm [8]. Engel et al [3] proposed a psychophysically calibrated controller that employs a cost function based on the noticeability of redirection. Nitzsche et al [12] and Su et al [19] suggested an approach that dynamically minimizes the introduced curvature, but does not make imperceptibility a primary goal.…”
Section: Related Workmentioning
confidence: 99%
“…The resulting J 0 (x 0 ) is the optimal cost and the minimization in (3) gives the set of optimal control laws µ k (x k ) for each stage k, see [1]. The control laws provide the optimal action u k for each state at the corresponding stage.…”
Section: Basic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Redirected Walking [16,21,10] and Motion Compression [13,7,22] techniques "trick" the user into walking in a curved path in the real world when walking in a straight line in the virtual world through the progressive rotation of the scene around them. In a sufficiently large workspace, and with a straight virtual path, the user can walk endlessly without reaching the limits of the real workspace.…”
Section: Redirection Techniquesmentioning
confidence: 99%
“…A group of techniques have been initiated to address this issue. Redirected walking is one technique used to subtly rotate the virtual environment, preventing users from encountering walls [11,6]. Distracting objects can help make these redirections less noticeable [10].…”
Section: Previous Workmentioning
confidence: 99%